Capturing the multilevel dynamics of emergence: Computational modeling, simulation, and virtual experimentation. (February 2016) - Kozlowski, Steve W. J.; Chao, Georgia T.; Grand, James A.; Braun, Michael T.; Kuljanin, Goran
Emergent phenomena—those that manifest bottom-up from the psychological characteristics, perceptions, and interactions among individuals—are a fundamental dynamic process in multilevel theory, but have been treated in a very limited way in the research literature. In particular, treatments are largely assumed (rather than observed directly), retrospective, and static. This paper describes a research paradigm designed to examine directly the dynamics of micro-meso—individual, dyad, and team—emergent phenomena. We identify, describe, and illustrate the sequence of theoretical, measurement, computational, data analytic, and systematic research activities that are necessary to operationalize and utilize the paradigm. We illustrate the paradigm development process using our research, focused on learning and team knowledge emergence, and highlight key design principles that can be applied to examine other emergent phenomena in teams. We conclude with a discussion of contributions, strengths and limitations, and generalization of the approach to other emergent phenomena in teams.